RANCANG BANGUN TOPI TUNA NETRA DENGAN 3 AKSES KONTROL SENSOR ULTRASOUND BERBASIS ARDUINO UNO - Susanta, Muhamad Hilmansyah; Sujana, Nana (Jurnal Teknologi Komputer dan Informatika, 2024)
Advances in science and technology are very helpful in human work. One of them is technological advances in the field of control systems. The use of microcontrollers really helps humans in carrying out their activities in daily life. One of its uses is in making tools to assist the blind in carrying out their activities. The blind hat with 3 Arduino-based ultrasound accesses is a tool for detecting distance with a range of 3 accesses, namely front, right side and left side. The components used in this tool include the Arduino Uno microcontroller, HC-SR 04 Ultrasound Sensor and DF Player and speakers. The Arduino Uno microcontroller is used as a data processor for both sensor input and actuator output. The use of the HC-SR04 Ultrasound sensor is used as a sensor for detecting obstacle distances. Meanwhile, the DF Player and Speaker are used as actuators. If the obstacle distance of the HC-SR04 sensor is under 40CM, the speaker will emit a sound according to the detected location so that the obstacle distance of an object can be detected by the blind from 3 access controls, namely the front, right side and left side.